PENGARUH KEPERCAYAAN, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUASAN DAN LOYALITAS NASABAH TABUNGAN PADA PD BPR BANK DAERAH KLATEN - Jarot Santosa; Denny Mahendra; Aris Tri Haryanto (STIE AUB Surakarta, 2019)
ABSTRACT The purpose of this research is to know and analyze empirically influence of trust, promotion and product quality on satisfaction and loyalty of customer of saving in PD. BPR of Bank Daerah Klaten. The analytical technique used is by using instrument test which includes validity test and reliability test, linearity test, regression analysis, path analysis, t test, F test, coefficient determination test and correlation analysis. Hypothesis test results trust has a significant effect on customer satisfaction. Promotion has a significant effect on customer satisfaction of savings. Product quality has a significant effect on customer satisfaction. Trust has no significant effect on customer savings loyalty. Promotion has a significant effect on customer savings loyalty. Product quality has no significant effect on loyalty. Satisfaction has a significant effect on customer savings loyalty. The result of F test can be concluded jointly variable of trust, promotion, product quality, and satisfaction influence to customer loyalty of saving PD. BPR of Bank Daerah Klaten. The total R2 result of 0.890 can be interpreted as the loyalty of customers of PD saving. BPR Bank Daerah Klaten explained by the variable of trust, promotion, product quality and satisfaction of 89% and the remaining 11% described other variables outside the research model as an example location, service quality and infrastructure facilities. The result of path analysis shows that the influence of trust through satisfaction is the most dominant influence in influencing customer loyalty of PD saving. BPR of Bank Daerah Klaten. Keywords: Trust, Promotion, Product Quality, Satisfaction, Loyalty